Pengaruh Electronic Word Of Mouth, Brand Awareness, Dan Kepercayaan Pelanggan Terhadap Loyalitas Pelanggan Tokopedia Di Kota Malang - Asnawati, Zubaidah Ajeng; Salim, Muhammad Agus; Priyono, Achmad Agus (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Electronic Word of Mouth, Brand Awareness, and Customer Trust on Customer Loyalty to Tokopedia in Malang City. In this study, the population size is unknown. Therefore, this study used the Malhotra formula to determine the number of samples, obtaining results of 5 respondents. This research uses primary and secondary data and the data collection method used is an online questionnaire. (Google Forms). For data analysis, Version 25 software is used to analyze instrument tests, classical assumption tests, multiple linear tests, and hypothesis tests. The results of this research show that the Electronic Word of Mouth variable has no effect on Tokopedia Customer Loyalty in Malang City. The Brand Awareness variable has no effect on Tokopedia Customer Loyalty in Malang City. Customer Trust has a significant effect on Tokopedia Customer Loyalty in Malang City. Kata Kunci : Electronic Word of Mouth, Brand Awareness, Customer Trust, Customer Loyalty.